2022
DOI: 10.3390/ijerph19053092
|View full text |Cite
|
Sign up to set email alerts
|

Toxic and Nutritional Optic Neuropathies—An Updated Mini-Review

Abstract: Optic neuropathies constitute a group of conditions with various etiologies and might be caused by different factors; we can distinguish the genetic and acquired causes of optic neuropathies. Even though the symptoms are not highly specific, this condition is primarily characterized by unilateral or bilateral vision loss with worsening color detection. The loss may be acute or gradual depending on the causation. In this article, we included a specification of toxic optic neuropathy (TON) mainly triggered by al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 140 publications
0
17
0
Order By: Relevance
“…As patients overrepresent some human leukocyte antigens, genetic predisposition to optic neuritis seems to be of importance [ 32 , 33 , 34 , 35 , 36 ]. Studies have shown that chronic exposure to heavy metals may also contribute to optic neuropathy [ 37 ]. So far, cobalt (Co) neurotoxicity, leading to visual impairment and loss of vision, has been confirmed [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…As patients overrepresent some human leukocyte antigens, genetic predisposition to optic neuritis seems to be of importance [ 32 , 33 , 34 , 35 , 36 ]. Studies have shown that chronic exposure to heavy metals may also contribute to optic neuropathy [ 37 ]. So far, cobalt (Co) neurotoxicity, leading to visual impairment and loss of vision, has been confirmed [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing incidence of nutritional optic neuropathy may be related to the widespread of gastric bypass surgeries and vegan diets. 9,24 However, the causal connection remains unproven and very few unequivocally confirmed cases of optic neuropathy are described to be caused by a identified single toxin or nutrient deficiency. 25 The pathophysiology in both forms involve in biochemical pathways of cell energy metabolism, oxidative stress and free radicals, triggering dysfunction of the ON.…”
Section: Toxic/nutritional Optic Neuropathymentioning
confidence: 99%
“…Therefore, cells like neurons that acquire their energy mostly from aerobic reactions are more vulnerable to hypoxia. [1][2][3] So, methanol can lead to optic neuropathy through this mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Formic acid has an inhibitory effect on cytochrome C oxidase, an enzyme in the aerobic respiration pathway, and causes cell hypoxia. Therefore, cells like neurons that acquire their energy mostly from aerobic reactions are more vulnerable to hypoxia 1–3 . So, methanol can lead to optic neuropathy through this mechanism.…”
Section: Introductionmentioning
confidence: 99%